(untitled) (Perner’s Contacts, 2009)
This contribution presents a possible implementation of an electronic data form for processing of all technological operations, especially on transoceanic vessels. The continuous diagnostics carried out using this form helps to prevent failures, which increases voyage safety, resulting in reduction of operating costs, and also decreases workload of engineer officers, especially during intercontinental voyages.